Transnational Islamic Infiltration in Indonesia - Idris, Akhmad Nizar (Cakrawala : Jurnal Kajian Manajemen Pendidikan Islam dan Studi Sosial, 2025)
Transnational Islam is a movement that is not limited by national borders, it has an influence on the thoughts, ideology and policies of a country. This article will discuss topics related to Transnational Islamic Infiltration in Indonesia by examining the historical development, ideology, and characteristics of transnational Islamic movements such as the Muslim Brotherhood, Hizb ut Tahrir and Salafi Wahabi. Based on a survey conducted by Alvara Research and Wahid Institute, it was found that some Indonesians show intolerant and radical attitudes influenced by transnational Islamic movements. This research uses a qualitative method and discourse analysis approach. This research tries to examine data from various literature related to Transnational Islam and its infiltration. In addition, this research also examines various surveys that measure the level of radicalism and intolerance in Indonesia. The results of this study show that Transnational Islam has a political agenda in the form of formalising Islamic sharia and establishing an Islamic caliphate that transcends national boundaries and contradicts the Unitary State of the Republic of Indonesia (NKRI). This research recommends that in studying and understanding Islam, it is necessary to use a contextual approach in order to maintain harmonious values and Islam.